Targeting mitochondria to oppose the progression of nonalcoholic fatty liver disease - Grattagliano, Ignazio (2019)
Nonalcoholic fatty liver disease (NAFLD) is a condition characterized by the excessive accumulation of triglycerides in hepatocytes. NAFLD is the most frequent chronic liver disease in developed countries, and is often associated with metabolic disorders such as obesity and type 2 diabetes. NAFLD definition encompasses a spectrum of chronic liver abnormalities, ranging from simple steatosis (NAFL), to steatohepatitis (NASH), significant liver fibrosis, cirrhosis, and hepatocellular carcinoma. NAFLD, therefore, represents a global public health issue. Mitochondrial dysfunction occurs in NAFLD, and contributes to the progression to the necro-inflammatory and fibrotic form (NASH). Disrupted mitochondrial function is associated with a decrease in the energy levels and impaired redox balance, and negatively affects cell survival by altering overall metabolism and subcellular trafficking. Such events reduce the tolerance of hepatocytes towards damaging hits, and favour the injurious effects of extra-cellular factors. Here, we discuss the role of mitochondria in NAFLD and focus on potential therapeutic approaches aimed at preserving mitochondrial function.